Análise do uso de coagulantes orgânicos no tratamento de efluente industrial gerado no processo de fiação de seda - Silva, Gabriele Lopes (2019)
The silk yarn’s process generates large amount of effluent due to production process flow. Silk industry effluent are sources of serycin since it is removed from the silk yarn in the baking process, where the cocoons are cooked in hot water under pressure to soften the serycin gum, making the Fibers unroll more easily. Considering the risk of environmental pollution, which can be caused due to the release of this effluent in the receiving hydrous bodies, the treatment of the effluent becomes essential. Knowing the pollutant potential of the effluent under study, a comparison between the application of two different organic coagulants (extracted from the seed of Moringa oleifera and Tanino) was proposed for different conditions of the treatment process. The experiment was carried out in Jar-Test using pre - established coagulant concentration, and the whole procedure was performed in triplicate with collections at 10, 30, 50 and 70 minutes of Sedimentation. The parameters of apparent color, turbidity, electrical conductivity, pH, chemical oxygen demand, dissolved solids and total solids were analyzed. The best results for apparent color removal were obtained using the Moringa oleifera coagulant due to high efficiency before and after the filtration process, as well as the turbidity parameter. It was observed on analysis of dissolved solids that the coagulant with greater efficiency was Tanino. It is noted in the essays before the filtration process, the removal values of both coagulants, remained constant over the 70 minutes of sedimentation, but the Tanino already presented higher removal efficiency when compared to Moringa. The best results for COD were obtained with the use of Moringa oleifera. Thus, after the present study, the application of Moringa oleifera Coagulant is recommended for the treatment of this specific effluent due to its high efficiency in both sedimentation and filtration processes.